Resepsi Al-Qur’an di Media Sosial (Studi atas Pengamalan QS. Yāsīn [36]: 82 di TikTok) - Rifai, masyhuri rifai; Alda, Alda; Has, Hasdin (Jurnal Riset Agama, 2025)
Social media has transformed the way society interacts with religious texts, including the Qur'an. This study aims to uncover an intriguing phenomenon regarding the reception and practice of QS. Yāsīn [36]: 82 among TikTok users, particularly in relation to its use as a means of attracting affection. The study employs a 'living Qur'an' approach using qualitative methods through TikTok content observation, in-depth interviews with five informants, and document analysis. The findings reveal a significant gap between the interpretations of classical and contemporary scholars and those of TikTok users. While traditional exegetes interpret this verse as an affirmation of God's omnipotence in creation, some TikTok users view it as a formula to attract love, fulfill desires, or even as a tool for revenge. The transmission of such understanding occurs through spiritual networks rooted in Sufi teachings which then undergo a transformation in meaning and practice as they spread through social media.